Criterion for the uniqueness of a solution of the Darboux-Protter problem for multidimensional Hyperbolic equations with Chaplygin operator - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain a criterion for the uniqueness of a regular solution of the Darboux-Protter problem for multidimensional hyperbolic equations with Chaplygin operator. We also prove a theorem on the uniqueness of solutions of the dual problem.